INTERNET AS A FORM OF CIVIL SOCIETY - Krasnova,; Kireenkova, Zoya; Zorina, Natalya; Kortunov, Vadim (Revista Inclusiones, 2019)
An attempt to resolve (or at least to consider) the problem of civil activity sooner or later leads to the issue of civil society. The relation between them is not only etymological, but also essential. The structure of the civil society is so complex that it sometimes makes it impossible to predict the results of the activities performed by certain social forces. The presence of various social movements is an evidence of the developed civil society. In order to prove this idea, it is necessary to consider the problem of the civil society in the historical process.